Relationship Between Mental Imagery And Speed Of Refereeing Decision-Making Among Badminton Referees In Iraq - Taha Youssef Karim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to analyze relationship between mental imagery and speed of refereeing decision-making among badminton referees in Iraq, as it is one of the games that require a high level of mental concentration and the ability to respond quickly to changing situations. The researcher adopted the descriptive correlational approach for its suitability to the nature of the study, and a sample of (30) referees was selected representing different refereeing levels international, Asian, first, second, third). The study used a modified mathematical mental imagery scale, as well as a validated test based on real-life situations, to measure decision-making speed. Both instruments were examined by a panel of experts to ensure validity and reliability. The results showed a statistically significant positive correlation between mental imagery and decision-making speed. Significant differences also emerged between referees' levels, with international and Asian referees having higher levels in both variables compared to referees from local levels . The study recommends integrating mental skills as an essential part of referee preparation and development programs, and intensifying mental training alongside skill and cognitive training. It also suggests conducting similar studies in other sports, examining the impact of factors such as psychological stress or gender on decision-making speed. This study reflects the importance of mental imagery in refereeing performance and provides a scientific basis for developing sports refereeing in Iraq, especially in fast-paced games.